2012
DOI: 10.1364/oe.20.005402
|View full text |Cite
|
Sign up to set email alerts
|

A microfiber coupler tip thermometer

Abstract: A compact thermometer based on a broadband microfiber coupler tip is demonstrated. This sensor can measure a broad temperature interval ranging from room temperature to 1283 ºC with sub-200 µm spatial resolution. An average sensitivity of 11.96 pm/ºC was achieved for a coupler tip with ~2.5 µm diameter. This is the highest temperature measured with a silica optical fiber device.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
47
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
2
2

Relationship

4
4

Authors

Journals

citations
Cited by 79 publications
(48 citation statements)
references
References 24 publications
(30 reference statements)
0
47
0
Order By: Relevance
“…This microfiber coupler has many potential applications, for example in high performance fiber lasers, fiber sensors and optical coherence tomography systems. Furthermore MFC based thermometers [9], [10] and ultra-broadband 3 dB coupler [11] have also been demonstrated recently. Earlier research on the dependence of the coupling coefficient of traditional fused bi-conical tapered couplers on the external RI has been presented and it has been shown that it is possible to use such a structure to develop a fiber based refractometer [12], [13].…”
mentioning
confidence: 99%
“…This microfiber coupler has many potential applications, for example in high performance fiber lasers, fiber sensors and optical coherence tomography systems. Furthermore MFC based thermometers [9], [10] and ultra-broadband 3 dB coupler [11] have also been demonstrated recently. Earlier research on the dependence of the coupling coefficient of traditional fused bi-conical tapered couplers on the external RI has been presented and it has been shown that it is possible to use such a structure to develop a fiber based refractometer [12], [13].…”
mentioning
confidence: 99%
“…The sensor resolution R is defined as the minimum temperature change that the sensor can distinguish. Since the power resolution of the OSA (and commonly of many powermeters) is 10 -3 dB, an average R~0.66 ºC was achieved in the temperature range ~85.3 ºC to ~1511 ºC; this is higher than that obtained measuring the peak shift [11]. Better resolutions can be potentially achieved with smaller size MFCTs and signal processing.…”
Section: High Temperature Measurementmentioning
confidence: 97%
“…In ref. [11], a compact thermometer based on a MFCT was reported: by measuring wavelength shifts, it measured a broad temperature interval ranging from room temperature to 1283 ºC with ~2.5 µm diameter tip. In this paper, a MFCT with minimum diameter of ~12.56 µm was chosen to ensure an adequate rigidity for the thermometer head and a wide temperature measurement range, even if this potentially resulted in multimode guidance.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently highly sensitive temperature sensors based on a full or half microfiber coupler (MFC) have been presented [6,7]. The maximum sensitivity of such sensors can reach circa 36.6 pm/°C, which is comparable to that achievable with the conventional optical fiber temperature sensors.…”
Section: Introductionmentioning
confidence: 99%